Ash removal from various spent liquors by oxidation process for bio-carbon production. Issue 2 (April 2020) - Al-Kaabi, Zainab; Pradhan, Ranjan; Thevathasan, Naresh; Gordon, Andrew; Chiang, Yi Wai; Arku, Precious; Dutta, Animesh
Abstract: The application of black (spent) liquors for bio-carbon production is a promising method to add value to this industrial renewable waste stream. Further valorization by conversion to higher grade bio-carbon products may significantly enhance their adoption to various industrial uses. To increase the purity of the bio-carbon by selective removal of minerals and ash, a novel oxidative procedure performed at room temperature was developed and its potential was evaluated. The procedure was carried out with hydrogen peroxide (H2 O2 ) as oxidant on three different types of spent liquor, namely neutral sulphite semi-chemical spent liquor (NSSCSL) sourced from recycled paper, softwood (pine and spruce) kraft spent liquor (PSKSL), and hardwood (aspen and balsam poplar) kraft spent liquor (APKSL). The efficiency of the oxidation procedure on each raw material was studied and reported. The maximum mass yield of bio-carbon was 31.88%, 46.27% and 43.93% after the ash removal processing of NSSCSL, PSKSL, and APKSL spent liquors respectively. The maximum efficiency for mineral and ash removal from spent liquors achieved were 94.63%, 98.08 %, and 94.93% respectively for the three types of spent liquors. The highest heating values (HHV) demonstrated in the bio-carbon produced were 26.11 MJ/kg, 24.74 MJ/kg, and 26.89 MJ/kg respectively. Empirical indices were also calculated to establish and characterize bio-carbons potential for its combustion quality as a function of this oxidation process. The upgraded bio-carbon appears to enhance their potential as environment friendly, green substitutes for solid fuel and bio-material applications.